High-adsorbability non-woven fabric as well as preparation method and application thereof
By combining modified activated carbon and modified chitosan-β-cyclodextrin polymer in non-woven fabrics, the efficient adsorption and selective removal capabilities of non-woven fabrics are achieved, which solves the problem of adsorption and solubility pollution of existing non-woven fabrics. It solves the problem of low chemical efficiency and significantly improves the purification effect of aquaculture environment.
Patent Information
- Application Number
- CN202411445731.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
AI Technical Summary
Existing non-woven fabrics are inefficient in adsorbing soluble pollutants such as nitrogen, phosphorus, heavy metal ions, etc., and lack selective adsorption capabilities, so they cannot effectively remove specific pollutants.
Adopt high adsorption non-woven fabrics composed of polypropylene, polyester particles, modified activated carbon and modified shell polycan-β cycle polymer. Through the synergy of physical adsorption and chemical adsorption, a variety of pollution in water is removed Best.
It significantly improves the adsorption efficiency and selectivity of non -woven fabrics, and can efficiently remove organic matter, inorganic ions, heavy metals, pigment and odor, etc., and improve the aquaculture environment.
Smart Images

Figure BDA0005087689130000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonwoven fabrics, and in particular to a highly adsorbent nonwoven fabric and a preparation method and application thereof. Background Art
[0002] As one of the important economic pillar industries in my country, aquaculture is facing increasingly serious water pollution problems as the scale of aquaculture expands and the degree of intensiveness increases. Pollutants such as leftover bait, feces, and debris generated during the aquaculture process mainly exist in the water in the form of suspended particles, and also include nutrients such as nitrogen and phosphorus, as well as toxic substances such as heavy metal ions. As the aquaculture method develops towards recirculating aquaculture, the aquaculture density and feeding amount have greatly increased, resulting in a corresponding increase in the amount of leftover bait and fish excrement, causing ultrafine suspended particles to remain in the aquaculture system for a long time, causing many hazards to the aquaculture environment, such as damaging fish gills, blocking biological filters, ammoniation to produce ammonia nitrogen, consuming dissolved oxygen in the water, and adsorbing a large number of bacteria, viruses and other microorganisms, resulting in a decrease in the self-purification capacity of the water.
[0003] At present, the commonly used water purification methods in aquaculture mainly include physical filtration, biological filtration, chemical treatment, etc. Among them, physical filtration is a simple and effective method, usually using porous materials such as sand, non-woven fabrics, etc. as filter media. Chinese patent CN201310029483.3 discloses a composite filter medium and a method for filtering ultrafine suspended matter in seawater aquaculture water. The composite filter medium includes a primary filter layer and a precision non-woven fabric layer, and the precision non-woven fabric layer is attached to the back surface of the primary filter layer. The primary filter layer is an asymmetric filter medium, and its pore size gradually changes from large to small. The average pore size of the front surface of the primary filter layer is 20-60 μm, the average pore size of the back surface is 10-30 μm, and the thickness is 3-5 mm; the average pore size of the precision non-woven fabric layer is 5-20 μm, and the thickness is 100-400 μm. In this technical solution, suspended particles are filtered by changing the pore size of the non-woven fabric, and the risk of organic matter clogging the pores is reduced by hydrophilic modification of the non-woven fabric. However, the above technical solution still has the following problems: 1. The adsorption capacity for soluble pollutants such as nitrogen, phosphorus, heavy metal ions, etc. is limited; 2. Although hydrophilic modification can reduce the adsorption of certain organic matter, it lacks selective adsorption capacity for various types of pollutants in aquaculture and cannot remove specific pollutants in a targeted manner. Summary of the invention
[0004] In view of this, the present invention proposes a highly adsorbent non-woven fabric and a preparation method and application thereof, so as to solve the problems of low adsorption efficiency and poor adsorption selectivity of non-woven fabrics in the prior art.
[0005] The technical solution of the present invention is achieved in this way:
[0006] In the first aspect, the present invention provides a high-adsorbability non-woven fabric, which is obtained by immersing a non-woven fabric base fabric in a finishing liquid, and the non-woven fabric base fabric is made of the following raw materials: by weight, 70-80 parts of polypropylene, 15-55 parts of polyester particles, 5-10 parts of modified activated carbon, 3-5 parts of lubricant, 5-10 parts of antioxidant, 1-2 parts of heat stabilizer, and 5-8 parts of compatibilizer.
[0007] In the present invention, polypropylene and polyester particles are used as basic materials to form non-woven fabrics, and modified activated carbon is added to remove organic matter (such as metabolites, etc.) and pollutants such as pigments and odors in water through physical adsorption and chemical adsorption mechanisms; the modified chitosan-β-cyclodextrin polymer in the finishing liquid removes anionic pollutants (such as phosphates, nitrates, etc.), heavy metal ions (copper, lead, mercury) and aromatic compounds in water through chemical adsorption and inclusion complexation. The combination of modified activated carbon and finishing liquid makes this non-woven fabric have multiple adsorption mechanisms, which can simultaneously remove multiple pollutants in aquaculture, including organic matter, inorganic ions, heavy metals, pigments and odor substances, etc., which not only improves the overall adsorption efficiency, but also enhances the selective adsorption capacity for specific pollutants.
[0008] On the basis of the above technical solution, preferably, the preparation method of the modified activated carbon comprises the following steps:
[0009] (1) ball milling the biomass activated carbon;
[0010] (2) The ball-milled biomass activated carbon and the activator are then mixed, placed in a tube furnace and heated to 600-800° C. under argon protection, and reacted at a constant temperature for 45-65 minutes to obtain modified activated carbon.
[0011] On the basis of the above technical scheme, preferably, the raw material of the biomass activated carbon is one or more of coconut shell, bamboo, rice straw, and corn straw; in step (1), the parameters of the ball milling treatment are: ball-to-material ratio 8-10:1, ball milling speed 300-400rpm, and ball milling time 2-4h.
[0012] On the basis of the above technical solution, preferably, the mass ratio of the biomass activated carbon to the activator is 1:1-3, the activator includes potassium carbonate and potassium bicarbonate, and the mass ratio of potassium carbonate to potassium bicarbonate is 3:1.
[0013] In the present invention, the biomass activated carbon is firstly subjected to ball milling treatment, and the particle size of the activated carbon is reduced by the mechanical action of ball milling, the specific surface area is increased, and a large number of structural defects and active sites are introduced into the carbon skeleton. At the same time, the mechanical force may also cause the breakage of certain chemical bonds in the carbon skeleton, forming free radicals and unsaturated bonds, which all increase the chemical reactivity of the activated carbon. Then the biomass activated carbon after ball milling treatment is mixed with an activator for pyrolysis treatment, and under high temperature conditions, potassium carbonate and potassium bicarbonate are first thermally decomposed to generate potassium oxide, which undergoes redox reaction with the carbon in the activated carbon to form metallic potassium and carbon monoxide. This process not only etches the carbon skeleton and creates more pores, but also introduces oxygen-containing functional groups on the surface of the activated carbon; at the same time, metallic potassium will further insert into the carbon layer, causing the carbon layer to peel off and expand, forming more micropores and mesoporous structures, increasing the porosity, and greatly improving the adsorption capacity of the activated carbon for various pollutants. In addition, ball milling is performed first to increase the specific surface area, so that the activating agents (potassium carbonate and potassium bicarbonate) can penetrate more evenly and deeply into the internal structure of the activated carbon in the subsequent pyrolysis treatment. This deep penetration ensures that the activation process is carried out evenly throughout the volume of the activated carbon, rather than being limited to the surface. The synergistic treatment of ball milling and pyrolysis can make the modified activated carbon have a high specific surface area, rich pore structure and diverse surface functional groups, greatly improving its adsorption efficiency for various pollutants.
[0014] On the basis of the above technical solution, preferably, the preparation method of the finishing liquid comprises the following steps:
[0015] S1, adding chitosan to deionized water, reacting in a constant temperature oil bath at 75-85°C for 10-12h, then adding 2,3-epoxypropyltrimethylammonium chloride, continuing the reaction for 20-24h, cooling to room temperature after the reaction, filtering and drying to obtain quaternized chitosan;
[0016] S2, adding quaternized chitosan and β-cyclodextrin to deionized water, stirring and mixing evenly, then dissolving S-acetylthiosuccinic anhydride and p-toluenesulfonic acid in DMF and adding them to the aqueous solution, heating to 120-160° C., reacting for 30-40 minutes, and after the reaction is completed, washing, filtering and drying to obtain a chitosan-β-cyclodextrin polymer;
[0017] S3. First, mix the chitosan-β-cyclodextrin polymer and deionized water, then add sodium ethyl xanthate and sodium hydroxide, raise the temperature to 45-55° C., react for 1-3 hours, and after the reaction, precipitate with alcohol, wash, and dry to obtain a modified chitosan-β-cyclodextrin polymer; mix the modified chitosan-β-cyclodextrin polymer with deionized water to obtain a finishing solution.
[0018] Specifically, in step S1, the quaternization process introduces a large number of positive charges on the chitosan molecules. These positive charges can adsorb anionic pollutants in water, such as phosphates, sulfates, etc., through electrostatic interactions; at the same time, the quaternary ammonium group may increase the adhesion of the finishing liquid to the non-woven fabric through van der Waals forces and hydrophobic interactions. In step S2, S-acetylthiosuccinic anhydride reacts with the hydroxyl groups on the quaternized chitosan and β-cyclodextrin to cross-link the quaternized chitosan and β-cyclodextrin, and β-cyclodextrin is introduced into the chitosan structure. The composite material obtains a high-efficiency adsorption capacity for various organic pollutants, such as aromatic compounds, drug residues, pesticides, etc. in water; at the same time, the exterior of β-cyclodextrin is hydrophilic, and it can interact with the polar groups on the surface of the non-woven fabric through hydrogen bonds to further increase the adhesion. In step S3, the introduced xanthate group has a strong metal chelating ability, and forms a stable coordination compound with a variety of heavy metal ions, thereby achieving efficient adsorption of heavy metals. For example, it can effectively adsorb Cu 2+ , Pb 2+ 、Cd 2+ Modified chitosan-β-cyclodextrin polymer has multiple adsorption mechanisms. Attaching it to non-woven fabrics can simultaneously treat a variety of pollutants in water, including inorganic ions, organic molecules and heavy metal ions.
[0019] On the basis of the above technical solution, preferably, in step S1, the mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:2-3.
[0020] On the basis of the above technical solution, preferably, in step S2, the mass ratio of the quaternized chitosan, β-cyclodextrin, S-acetylthiosuccinic anhydride and p-toluenesulfonic acid added is 2:4-6:2:0.2-0.4.
[0021] On the basis of the above technical solution, preferably, in step S3, the mass volume ratio of the chitosan-β-cyclodextrin polymer, sodium ethyl xanthate and sodium hydroxide is 1:0.3-0.4:0.02-0.05, and the sodium hydroxide is prepared into a sodium hydroxide solution with a mass percentage of 7.0%-8.0% and added.
[0022] On the basis of the above technical solution, preferably, in step S3, the mass concentration of the modified chitosan-β-cyclodextrin polymer in the finishing liquid is 0.4-0.6 g / L.
[0023] Based on the above technical scheme, preferably, the lubricant is polyethylene wax and / or paraffin, the antioxidant is antioxidant 168 and / or antioxidant 3125, the heat stabilizer is one or more of calcium stearate, magnesium stearate and glyceride, and the compatibilizer is maleic anhydride grafted polypropylene.
[0024] In a second aspect, the present invention provides a method for preparing a highly adsorbent nonwoven fabric, comprising the following steps:
[0025] (1) adding polypropylene, polyester particles and modified activated carbon into a mixer and mixing them evenly, then adding a lubricant, an antioxidant and a compatibilizer and mixing them evenly, granulating them through a twin-screw extruder, and vacuum drying to obtain a blend masterbatch;
[0026] (2) Melting the blend masterbatch by screw extrusion to obtain a melt, pressing the melt into a spinning box at a pressure of 1-3 MPa, spinning, cooling, and pulling to obtain a fiber web, and hot-rolling the obtained fiber web at 125-160° C. on a hot rolling mill to obtain a base fabric;
[0027] (3) placing the finishing liquid in a slurry barrel, passing the base fabric through a pressing roller and a sizing roller, placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure being 4-8 kg, the rolling line speed being 160-180 m / min, and then drying in an oven at 100-120° C. to a constant weight, thereby obtaining the highly absorbent nonwoven fabric.
[0028] In the present invention, by melt-blending the modified activated carbon with the base material, the modified activated carbon can be firmly embedded into the fiber structure of the non-woven fabric, reducing the risk of falling off, while increasing the distribution uniformity of the modified activated carbon, thereby improving the adsorption efficiency. The modified activated carbon is embedded in the fiber structure to form an inner adsorption layer, which mainly adsorbs organic pollutants, odors, etc.; the modified chitosan-β-cyclodextrin polymer in the finishing liquid is attached to the surface to form an outer adsorption layer, which mainly adsorbs heavy metal ions, anionic pollutants, etc. The synergistic effect of the two can improve the broad-spectrum adsorption performance on the one hand; on the other hand, the modified chitosan-β-cyclodextrin polymer on the surface can quickly capture pollutants, and the activated carbon in the inner layer can further adsorb, thereby improving the adsorption efficiency and prolonging the adsorption effect, which can accelerate the initial adsorption rate while maintaining a long-term adsorption effect.
[0029] In a third aspect, the present invention provides an application of a highly absorbent nonwoven fabric, wherein the nonwoven fabric is used for aquaculture. The nonwoven fabric can be made into a filter bag or a filter net, which is placed in a breeding pond to filter the water in the breeding pond; or the nonwoven fabric can be laid at the bottom of the breeding pond to absorb pollutants in the water and improve the breeding environment.
[0030] The highly absorbent nonwoven fabric and its preparation method and application of the present invention have the following beneficial effects compared with the prior art:
[0031] (1) By embedding modified activated carbon into the fiber structure of non-woven fabrics to form an inner layer of adsorption, and attaching modified chitosan-β-cyclodextrin polymer finishing liquid on the surface to form an outer layer of adsorption, a multi-level, broad-spectrum adsorption structure is formed. This structure realizes the synergistic effect of physical adsorption and chemical adsorption, and can efficiently remove various pollutants such as organic pollutants, heavy metal ions and inorganic anions in water, significantly improving the adsorption capacity and adsorption efficiency of non-woven fabrics, so that the material exhibits excellent performance in the treatment of complex water environments;
[0032] (2) The modified activated carbon used in the present invention has greatly increased its specific surface area and porosity through ball milling and high-temperature activation processes, thereby enhancing the physical adsorption capacity of the activated carbon for organic pollutants. The modified activated carbon is embedded in the fiber structure, providing a stable inner layer adsorption basis for the non-woven fabric, significantly improving the overall adsorption performance and service life of the material;
[0033] (3) A modified chitosan-β-cyclodextrin polymer finishing liquid was prepared, in which the quaternization process enhanced the electrostatic adsorption capacity for anionic pollutants, the introduction of β-cyclodextrin provided the inclusion capacity for organic molecules, and the introduction of xanthogenic acid groups gave the material a strong chelating ability for heavy metal ions. Through multiple modifications, the finishing liquid was able to specifically adsorb various pollutants, greatly expanding the application range and processing capacity of non-woven fabrics. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0036] Polypropylene was purchased from LyondellBasell Co., Ltd. with the product number RP348RX B and a melt index of 25 g / 10 min; antioxidant 168 was purchased from Hubei Wonder Chemical Company; antioxidant 3125 was purchased from Tianjin Alta Technology Co., Ltd.; chitosan was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a deacetylation degree ≥ 95% and a viscosity of 100-200 mPa.s, and the chitosan was water-soluble chitosan; β-cyclodextrin was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and maleic anhydride grafted polypropylene was purchased from Dongguan Dingxin Plastic Raw Materials Co., Ltd. with a grafting rate of 1.5% and a melt index of 130 g / 10 min.
[0037] Example 1
[0038] The present embodiment provides a highly adsorbent non-woven fabric and a preparation method thereof. The non-woven fabric is made of the following raw materials by weight: 75 g of polypropylene, 35 g of polyester particles, 8 g of modified activated carbon, 650 g of finishing liquid, 4 g of polyethylene wax, 1688 g of antioxidant, 1.5 g of calcium stearate, and 6.5 g of maleic anhydride grafted polypropylene. The preparation method of the non-woven fabric comprises the following steps:
[0039] (1) adding polypropylene, polyester particles and modified activated carbon into a mixer and mixing them evenly, then adding calcium stearate, antioxidant 168 and maleic anhydride grafted polypropylene and mixing them evenly, granulating them through a twin-screw extruder, and the temperatures (° C.) of each section of the extruder are 200, 210, 220, 240, 260, 255 and 250, and vacuum drying to obtain a blend masterbatch;
[0040] (2) the blend masterbatch is melted by screw extrusion at a melting temperature of 260° C. to obtain a melt, the melt is pressed into a spinning box at a pressure of 1-3 MPa, a fiber web is obtained by spinning, cooling, and pulling, and the obtained fiber web is hot-rolled on a hot rolling mill at 140° C. to obtain a base fabric;
[0041] (3) placing the finishing liquid in a slurry barrel, passing the base fabric through a pressing roller and a sizing roller, and placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure is 6 kg, the rolling line speed is 170 m / min, and then drying in an oven at 100-120° C. to constant weight, to obtain the highly absorbent nonwoven fabric;
[0042] The preparation method of modified activated carbon comprises the following steps:
[0043] (1) Coconut shell and bamboo were used as biomass raw materials, and pyrolysis carbonization was carried out at 600°C for 2 hours to obtain biomass activated carbon. 10 g of biomass activated carbon was ball milled, wherein the ball-to-material ratio was 9:1, the ball milling speed was 350 rpm, and the ball milling time was 3 hours;
[0044] (2) Then, 10 g of the ball-milled biomass activated carbon, 1.2 g of potassium carbonate, and 0.4 g of potassium bicarbonate were mixed, placed in a tube furnace and heated to 700° C. under argon protection, and reacted at a constant temperature for 50 min to obtain modified activated carbon.
[0045] Wherein, the preparation method of the finishing liquid comprises the following steps:
[0046] S1. Add 10 g of chitosan to 1000 mL of deionized water, react in a constant temperature oil bath at 80°C for 11 h, then weigh 25 g of 2,3-epoxypropyltrimethylammonium chloride and add it in 3 portions. After the addition is complete, continue to react for 22 h. After the reaction is completed, cool to room temperature, add 2000 mL of deionized water, ultrafilter to 500 mL, repeat ultrafiltration 3 times, and dry the ultrafiltered solution at 80°C to obtain quaternized chitosan;
[0047] S2, 10g of quaternized chitosan and 25g of β-cyclodextrin were added to 450mL of deionized water, and the mixture was stirred and mixed evenly. Then, 10g of S-acetylthiosuccinic anhydride and 1.5g of p-toluenesulfonic acid were dissolved in 60ml of DMF and added to the aqueous solution, and the mixture was heated to 140°C and reacted for 35min. After the reaction was completed, the solid was repeatedly washed with deionized water and ethanol to remove unreacted substances, and the obtained sample was placed in a vacuum drying oven and dried to constant weight at 60°C to obtain a chitosan-β-cyclodextrin polymer;
[0048] S3. First, 10g of chitosan-β-cyclodextrin polymer is mixed with 100ml of deionized water, and then 3.5g of sodium ethyl xanthate and 0.3g of sodium hydroxide are added, 0.3g of sodium hydroxide is dissolved in deionized water to prepare a 7.5wt.% sodium hydroxide solution, and the temperature is raised to 50°C, and the reaction is carried out for 2h. After the reaction is completed, the modified chitosan-β-cyclodextrin polymer is obtained by alcohol precipitation, washing, and drying; the modified chitosan-β-cyclodextrin polymer is mixed with deionized water to prepare a finishing liquid of 0.5g / L.
[0049] Example 2
[0050] This embodiment provides a highly adsorbent non-woven fabric and a preparation method thereof. The non-woven fabric is made of the following raw materials by weight: 70 g of polypropylene, 15 g of polyester particles, 5 g of modified activated carbon, 400 g of finishing liquid, 3 g of paraffin, 31255 g of antioxidant, 1 g of magnesium stearate, and 5 g of maleic anhydride grafted polypropylene. The preparation method of the non-woven fabric comprises the following steps:
[0051] (1) Add polypropylene, polyester particles and modified activated carbon into a mixer and mix them evenly, then add magnesium stearate, antioxidant 3125 and 5 g of maleic anhydride grafted polypropylene and mix them evenly, and granulate them through a twin-screw extruder. The temperature (° C.) of each section of the extruder is 200, 210, 220, 240, 260, 255 and 250° C., and vacuum dry to obtain a blend masterbatch;
[0052] (2) the blend masterbatch is melted by screw extrusion at a melting temperature of 240° C. to obtain a melt, the melt is pressed into a spinning box at a pressure of 1-3 MPa, a fiber web is obtained by spinning, cooling, and pulling, and the obtained fiber web is hot-rolled at 125° C. on a hot rolling mill to obtain a base fabric;
[0053] (3) placing the finishing liquid in a slurry barrel, passing the base fabric through a pressing roller and a sizing roller, placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure is 4 kg, the rolling line speed is 160 m / min, and then drying in an oven at 100° C. to constant weight, to obtain the highly absorbent nonwoven fabric;
[0054] The preparation method of modified activated carbon comprises the following steps:
[0055] (1) Coconut shell and bamboo were used as biomass raw materials, and pyrolysis carbonization was performed at 600°C for 2 hours to obtain biomass activated carbon. 10 g of biomass activated carbon was ball milled, wherein the ball-to-material ratio was 8:1, the ball milling speed was 300 rpm, and the ball milling time was 2 hours;
[0056] (2) Then, 10 g of the ball-milled biomass activated carbon, 0.75 g of potassium carbonate, and 0.25 g of potassium bicarbonate were mixed, placed in a tubular furnace and heated to 600° C. under argon protection, and reacted at a constant temperature for 65 min to obtain modified activated carbon.
[0057] Wherein, the preparation method of the finishing liquid comprises the following steps:
[0058] S1. Add 10 g of chitosan to 1000 mL of deionized water, react in a constant temperature oil bath at 75 ° C for 12 h, then weigh 20 g of 2,3-epoxypropyltrimethylammonium chloride and add it in 3 times. After the addition, continue to react for 20 h. After the reaction is completed, cool to room temperature, add 2000 mL of deionized water, ultrafilter to 500 mL, repeat ultrafiltration 3 times, dry the ultrafiltered solution at 80 ° C, and obtain quaternized chitosan;
[0059] S2, 10g of quaternized chitosan and 20g of β-cyclodextrin were added to 400mL of deionized water, and the mixture was stirred and mixed evenly. Then, 10g of S-acetylthiosuccinic anhydride and 1.0g of p-toluenesulfonic acid were dissolved in 50ml of DMF and added to the aqueous solution, and the mixture was heated to 120°C and reacted for 40min. After the reaction was completed, the solid was repeatedly washed with deionized water and ethanol to remove unreacted substances, and the obtained sample was placed in a vacuum drying oven and dried to constant weight at 60°C to obtain a chitosan-β-cyclodextrin polymer;
[0060] S3. First, 10g of chitosan-β-cyclodextrin polymer is mixed with 100ml of deionized water, and then 3.0g of sodium ethyl xanthate and 0.2g of sodium hydroxide are added. 0.2g of sodium hydroxide is dissolved in deionized water to prepare a 7wt.% sodium hydroxide solution, and the temperature is raised to 45°C. The reaction is carried out for 3h. After the reaction is completed, the modified chitosan-β-cyclodextrin polymer is obtained by alcohol precipitation, washing and drying; the modified chitosan-β-cyclodextrin polymer is mixed with deionized water to prepare a finishing liquid of 0.4g / L.
[0061] Example 3
[0062] The present embodiment provides a highly adsorbent non-woven fabric and a preparation method thereof. The non-woven fabric is made of the following raw materials by weight: 80 g of polypropylene, 55 g of polyester particles, 10 g of modified activated carbon, 800 g of finishing liquid, 5 g of polyethylene wax, 16810 g of antioxidant, 2 g of glyceride, and 8 g of maleic anhydride grafted polypropylene. The preparation method of the non-woven fabric comprises the following steps:
[0063] (1) adding polypropylene, polyester particles and modified activated carbon into a mixer and mixing them evenly, then adding polyethylene wax, antioxidant 168 and maleic anhydride grafted polypropylene and mixing them evenly, granulating through a twin-screw extruder, the temperature (° C.) of each section of the extruder being 200, 210, 220, 240, 260, 255 and 250, vacuum drying to obtain a blend masterbatch;
[0064] (2) the blend masterbatch is melted by screw extrusion at a melting temperature of 280° C. to obtain a melt, the melt is pressed into a spinning box at a pressure of 1-3 MPa, a fiber web is obtained by spinning, cooling, and pulling, and the obtained fiber web is hot-rolled on a hot rolling mill at 160° C. to obtain a base fabric;
[0065] (3) placing the finishing liquid in a slurry barrel, passing the base fabric through a pressing roller and a sizing roller, placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure is 8 kg, the rolling line speed is 180 m / min, and then drying in an oven at 120° C. to constant weight, to obtain the highly absorbent nonwoven fabric;
[0066] The preparation method of modified activated carbon comprises the following steps:
[0067] (1) Coconut shell and bamboo were used as biomass raw materials, and pyrolysis carbonization was carried out at 600°C for 2 hours to obtain biomass activated carbon. 10 g of biomass activated carbon was ball milled, wherein the ball-to-material ratio was 10:1, the ball milling speed was 400 rpm, and the ball milling time was 4 hours;
[0068] (2) Then, 10 g of the ball-milled biomass activated carbon, 2.25 g of potassium carbonate, and 0.75 g of potassium bicarbonate were mixed, placed in a tubular furnace and heated to 800° C. under argon protection, and reacted at a constant temperature for 45 min to obtain modified activated carbon.
[0069] Wherein, the preparation method of the finishing liquid comprises the following steps:
[0070] S1. Add 10 g of chitosan to 1000 mL of deionized water, react in a constant temperature oil bath at 85°C for 10 h, then weigh 30 g of 2,3-epoxypropyltrimethylammonium chloride and add it in 3 portions. After the addition, continue to react for 24 h. After the reaction is completed, cool to room temperature, add 2000 mL of deionized water, ultrafilter to 500 mL, repeat ultrafiltration 3 times, dry the ultrafiltered solution at 80°C, and obtain quaternized chitosan;
[0071] S2, 10g of quaternized chitosan and 30g of β-cyclodextrin were added to 500mL of deionized water, and the mixture was stirred and mixed evenly. Then, 10g of S-acetylthiosuccinic anhydride and 2.0g of p-toluenesulfonic acid were dissolved in 70ml of DMF and added to the aqueous solution, and the mixture was heated to 160°C and reacted for 30min. After the reaction was completed, the solid was repeatedly washed with deionized water and ethanol to remove unreacted substances, and the obtained sample was placed in a vacuum drying oven and dried to constant weight at 60°C to obtain a chitosan-β-cyclodextrin polymer;
[0072] S3. First, 10g of chitosan-β-cyclodextrin polymer is mixed with 100ml of deionized water, and then 4.0g of sodium ethyl xanthate and 0.5g of sodium hydroxide are added, 0.5g of sodium hydroxide is dissolved in deionized water to prepare an 8.0wt.% sodium hydroxide solution, and the temperature is raised to 55°C. The reaction is carried out for 1h. After the reaction is completed, the modified chitosan-β-cyclodextrin polymer is obtained by alcohol precipitation, washing and drying; the modified chitosan-β-cyclodextrin polymer is mixed with deionized water to prepare a finishing liquid of 0.6g / L.
[0073] Example 4
[0074] This embodiment provides a highly adsorbent non-woven fabric and a preparation method thereof. The non-woven fabric is made of the following raw materials by weight: 78 g of polypropylene, 30 g of polyester particles, 7 g of modified activated carbon, 500 g of finishing liquid, 3.5 g of polyethylene wax, 31259 g of antioxidant, 1.8 g of magnesium stearate, and 7 g of maleic anhydride grafted polypropylene; the preparation method of the non-woven fabric comprises the following steps:
[0075] (1) adding polypropylene, polyester particles and modified activated carbon into a mixer and mixing them evenly, then adding polyethylene wax, antioxidant 3125 and maleic anhydride grafted polypropylene and mixing them evenly, granulating through a twin-screw extruder, the temperature (° C.) of each section of the extruder being 200, 210, 220, 240, 260, 255 and 250, vacuum drying to obtain a blend masterbatch;
[0076] (2) the blend masterbatch is melted by screw extrusion at a melting temperature of 250° C. to obtain a melt, the melt is pressed into a spinning box at a pressure of 1-3 MPa, a fiber web is obtained by spinning, cooling, and pulling, and the obtained fiber web is hot-rolled at 150° C. on a hot rolling mill to obtain a base fabric;
[0077] (3) placing the finishing liquid in a slurry barrel, passing the base fabric through a pressing roller and a sizing roller, placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure is 7 kg, the rolling line speed is 175 m / min, and then drying in an oven at 110° C. to constant weight, to obtain the highly absorbent nonwoven fabric;
[0078] The preparation method of modified activated carbon comprises the following steps:
[0079] (1) Coconut shell and bamboo were used as biomass raw materials, and pyrolysis carbonization was performed at 600°C for 2 hours to obtain biomass activated carbon. 10 g of biomass activated carbon was ball milled, wherein the ball-to-material ratio was 9:1, the ball milling speed was 300 rpm, and the ball milling time was 3.5 hours;
[0080] (2) Then, 10 g of the ball-milled biomass activated carbon, 1.8 g of potassium carbonate, and 0.6 g of potassium bicarbonate were mixed, placed in a tube furnace and heated to 750° C. under argon protection, and reacted at a constant temperature for 60 min to obtain modified activated carbon.
[0081] Wherein, the preparation method of the finishing liquid comprises the following steps:
[0082] S1. Add 10 g of chitosan to 1000 mL of deionized water, react in a constant temperature oil bath at 75°C for 12 h, then weigh 25 g of 2,3-epoxypropyltrimethylammonium chloride and add it in three portions. After the addition is complete, continue to react for 23 h. After the reaction is completed, cool to room temperature, add 2000 mL of deionized water, ultrafilter to 500 mL, repeat ultrafiltration three times, and dry the ultrafiltered solution at 80°C to obtain quaternized chitosan;
[0083] S2, 10g of quaternized chitosan and 28g of β-cyclodextrin were added to 500mL of deionized water, and the mixture was stirred and mixed evenly. Then, 10g of S-acetylthiosuccinic anhydride and 1.8g of p-toluenesulfonic acid were dissolved in 65ml of DMF and added to the aqueous solution, and the mixture was heated to 130°C and reacted for 35min. After the reaction was completed, the solid was repeatedly washed with deionized water and ethanol to remove unreacted substances, and the obtained sample was placed in a vacuum drying oven and dried to constant weight at 60°C to obtain a chitosan-β-cyclodextrin polymer;
[0084] S3. First, 10g of chitosan-β-cyclodextrin polymer and 100ml of deionized water are mixed, and then 3.2g of sodium ethyl xanthate and 0.4g of sodium hydroxide are added, 0.4g of sodium hydroxide is dissolved in deionized water to prepare a 7.5wt.% sodium hydroxide solution, and the temperature is raised to 50°C, and the reaction is carried out for 2.5h. After the reaction is completed, the modified chitosan-β-cyclodextrin polymer is obtained by alcohol precipitation, washing, and drying; the modified chitosan-β-cyclodextrin polymer is mixed with deionized water to prepare a finishing liquid of 0.6g / L.
[0085] Comparative Example 1
[0086] The present embodiment provides a highly adsorbent non-woven fabric and a preparation method thereof. The non-woven fabric is made of the following raw materials by weight: 75 g of polypropylene, 35 g of polyester particles, 8 g of biomass activated carbon, 650 g of finishing liquid, 4 g of polyethylene wax, 1688 g of antioxidant, 1.5 g of calcium stearate, and 6.5 g of maleic anhydride grafted polypropylene; the preparation method of the non-woven fabric comprises the following steps:
[0087] (1) adding polypropylene, polyester particles and modified activated carbon into a mixer and mixing them evenly, then adding calcium stearate, antioxidant 168 and maleic anhydride grafted polypropylene and mixing them evenly, granulating them through a twin-screw extruder, and the temperatures (° C.) of each section of the extruder are 200, 210, 220, 240, 260, 255 and 250, and vacuum drying to obtain a blend masterbatch;
[0088] (2) the blend masterbatch is melted by screw extrusion at a melting temperature of 260° C. to obtain a melt, the melt is pressed into a spinning box at a pressure of 1-3 MPa, a fiber web is obtained by spinning, cooling, and pulling, and the obtained fiber web is hot-rolled on a hot rolling mill at 140° C. to obtain a base fabric;
[0089] (3) placing the finishing liquid in a slurry barrel, passing the base fabric through a pressing roller and a sizing roller, placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure being 6 kg, the rolling line speed being 170 m / min, and then drying in an oven at 100-120° C. to a constant weight, thereby obtaining the highly absorbent nonwoven fabric.
[0090] The preparation method of biomass activated carbon includes: using coconut shell and bamboo as biomass raw materials, performing pyrolysis and carbonization at 600° C. for 2 hours to obtain biomass activated carbon.
[0091] Wherein, the preparation method of the finishing liquid comprises the following steps:
[0092] S1. Add 10 g of chitosan to 1000 mL of deionized water, react in a constant temperature oil bath at 80°C for 11 h, then weigh 25 g of 2,3-epoxypropyltrimethylammonium chloride and add it in 3 portions. After the addition is complete, continue to react for 22 h. After the reaction is completed, cool to room temperature, add 2000 mL of deionized water, ultrafilter to 500 mL, repeat ultrafiltration 3 times, and dry the ultrafiltered solution at 80°C to obtain quaternized chitosan;
[0093] S2, 10g of quaternized chitosan and 25g of β-cyclodextrin were added to 450mL of deionized water, and the mixture was stirred and mixed evenly. Then, 10g of S-acetylthiosuccinic anhydride and 1.5g of p-toluenesulfonic acid were dissolved in 60ml of DMF and added to the aqueous solution, and the mixture was heated to 140°C and reacted for 35min. After the reaction was completed, the solid was repeatedly washed with deionized water and ethanol to remove unreacted substances, and the obtained sample was placed in a vacuum drying oven and dried to constant weight at 60°C to obtain a chitosan-β-cyclodextrin polymer;
[0094] S3. First, 10g of chitosan-β-cyclodextrin polymer is mixed with 100ml of deionized water, and then 3.5g of sodium ethyl xanthate and 0.3g of sodium hydroxide are added, 0.3g of sodium hydroxide is dissolved in deionized water to prepare a 7.5wt.% sodium hydroxide solution, and the temperature is raised to 50°C, and the reaction is carried out for 2h. After the reaction is completed, the modified chitosan-β-cyclodextrin polymer is obtained by alcohol precipitation, washing, and drying; the modified chitosan-β-cyclodextrin polymer is mixed with deionized water to prepare a finishing liquid of 0.5g / L.
[0095] Comparative Example 2
[0096] The present embodiment provides a highly adsorbent non-woven fabric and a preparation method thereof. The non-woven fabric is made of the following raw materials by weight: 75 g of polypropylene, 35 g of polyester particles, 8 g of modified activated carbon, 650 g of finishing liquid, 4 g of polyethylene wax, 1688 g of antioxidant, 1.5 g of calcium stearate, and 6.5 g of maleic anhydride grafted polypropylene. The preparation method of the non-woven fabric comprises the following steps:
[0097] (1) adding polypropylene, polyester particles, and modified activated carbon into a mixer and mixing them uniformly, then adding calcium stearate, antioxidant 168, and maleic anhydride grafted polypropylene and mixing them uniformly, granulating the mixture through a twin-screw extruder, wherein the temperature (° C.) of each section of the extruder is 200, 210, 220, 240, 260, 255, and 250° C., vacuum drying is performed to obtain a blend masterbatch, vacuum drying the blend masterbatch, and after drying, extruding the mixture through a screw extruder to melt the mixture, wherein the melting temperature is 260° C., to obtain a melt;
[0098] (2) Pressing the melt into a spinning box at a pressure of 1-3 MPa, spinning, cooling, and pulling to obtain a fiber web, and hot-rolling the obtained fiber web at 140° C. on a hot rolling mill to obtain a base fabric;
[0099] (3) placing the finishing liquid in a slurry barrel, passing the base fabric through a pressing roller and a sizing roller, and placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure is 6 kg, the rolling line speed is 170 m / min, and then drying in an oven at 100-120° C. to constant weight, to obtain the highly absorbent nonwoven fabric;
[0100] The preparation method of modified activated carbon comprises the following steps:
[0101] (1) Coconut shell and bamboo were used as biomass raw materials, and pyrolysis carbonization was carried out at 600°C for 2 hours to obtain biomass activated carbon. 10 g of biomass activated carbon was ball milled, wherein the ball-to-material ratio was 9:1, the ball milling speed was 350 rpm, and the ball milling time was 3 hours;
[0102] (2) Then, 10 g of the ball-milled biomass activated carbon, 1.2 g of potassium carbonate, and 0.4 g of potassium bicarbonate were mixed, placed in a tube furnace and heated to 700° C. under argon protection, and reacted at a constant temperature for 50 min to obtain modified activated carbon.
[0103] Wherein, the preparation method of the finishing liquid comprises the following steps:
[0104] S1. Add 10g chitosan to 1000mL deionized water, react in a constant temperature oil bath at 80℃ for 11h, then weigh 25g 2,3-epoxypropyltrimethylammonium chloride and add it in 3 times. After the addition, continue to react for 22h. After the reaction is completed, cool to room temperature, add 2000mL deionized water, ultrafilter to 500mL, repeat ultrafiltration 3 times, dry the ultrafiltered solution at 80℃ to obtain quaternized chitosan; mix the quaternized chitosan with deionized water to prepare a finishing solution of 0.5g / L.
[0105] Comparative Example 3
[0106] This embodiment provides a highly adsorbent nonwoven fabric and a preparation method thereof. The nonwoven fabric is made of the following raw materials by weight: 75 g of polypropylene, 35 g of polyester particles, 8 g of modified activated carbon, 650 g of finishing liquid, 4 g of polyethylene wax, 1688 g of antioxidant, 1.5 g of calcium stearate, and 6.5 g of maleic anhydride grafted polypropylene;
[0107] The method for preparing the nonwoven fabric comprises the following steps:
[0108] (1) adding polypropylene, polyester particles and modified activated carbon into a mixer and mixing them evenly, then adding calcium stearate, antioxidant 168 and maleic anhydride grafted polypropylene and mixing them evenly, granulating them through a twin-screw extruder, and the temperatures (° C.) of each section of the extruder are 200, 210, 220, 240, 260, 255 and 250, and vacuum drying to obtain a blend masterbatch;
[0109] (2) the blend masterbatch is melted by screw extrusion at a melting temperature of 260° C. to obtain a melt, the melt is pressed into a spinning box at a pressure of 1-3 MPa, a fiber web is obtained by spinning, cooling, and pulling, and the obtained fiber web is hot-rolled on a hot rolling mill at 140° C. to obtain a base fabric;
[0110] (3) placing the finishing liquid in a slurry barrel, passing the base fabric through a pressing roller and a sizing roller, and placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure is 6 kg, the rolling line speed is 170 m / min, and then drying in an oven at 100-120° C. to constant weight, to obtain the highly absorbent nonwoven fabric;
[0111] The preparation method of modified activated carbon comprises the following steps:
[0112] (1) Coconut shell and bamboo were used as biomass raw materials, and pyrolysis carbonization was carried out at 600°C for 2 hours to obtain biomass activated carbon. 10 g of biomass activated carbon was ball milled, wherein the ball-to-material ratio was 9:1, the ball milling speed was 350 rpm, and the ball milling time was 3 hours;
[0113] (2) Then, 10 g of the ball-milled biomass activated carbon, 1.2 g of potassium carbonate, and 0.4 g of potassium bicarbonate were mixed, placed in a tube furnace and heated to 700° C. under argon protection, and reacted at a constant temperature for 50 min to obtain modified activated carbon.
[0114] Wherein, the preparation method of the finishing liquid comprises the following steps:
[0115] S1. Add 10 g of chitosan to 1000 mL of deionized water, react in a constant temperature oil bath at 80°C for 11 h, then weigh 25 g of 2,3-epoxypropyltrimethylammonium chloride and add it in 3 portions. After the addition is complete, continue to react for 22 h. After the reaction is completed, cool to room temperature, add 2000 mL of deionized water, ultrafilter to 500 mL, repeat ultrafiltration 3 times, and dry the ultrafiltered solution at 80°C to obtain quaternized chitosan;
[0116] S2. Add 10g of quaternized chitosan and 25g of β-cyclodextrin to 450mL of deionized water, stir and mix evenly, then dissolve 10g of S-acetylthiosuccinic anhydride and 1.5g of p-toluenesulfonic acid in 60ml of DMF and add the mixture to the aqueous solution, heat to 140°C, react for 35min, and after the reaction is completed, repeatedly wash the obtained solid with deionized water and ethanol to remove unreacted substances, place the obtained sample in a vacuum drying oven, and dry it to constant weight at 60°C to obtain a chitosan-β-cyclodextrin polymer; mix the chitosan-β-cyclodextrin polymer with deionized water to prepare a 0.5g / L finishing solution.
[0117] Performance Testing
[0118] Prepare aqueous solution to simulate aquaculture environment, where pollutants include: 1mg / L butyl phthalate, heavy metal ions (including 2mg / L Cu 2+ 、2mg / LPb 2+ 、2mg / LCd 2+ ), 2mg / L potassium dihydrogen phosphate, 1mg / L potassium nitrate, simulate freshwater aquaculture environment. The above aqueous solution was passed through the non-woven fabrics prepared in the embodiments and comparative examples at a flow rate of 4L / h, and then the heavy metals after passing were detected. The concentration of heavy metal ions in the aqueous solution was tested by ICP, the concentration of phosphate and nitrate was detected by spectrophotometry, and the concentration of butyl phthalate was detected by high-performance liquid chromatography, and the removal rate of pollutants was calculated. The test results are shown in Table 1.
[0119] Table 1 Pollutant removal rate
[0120]
[0121] As can be seen from Table 1, the non-woven fabric prepared by the present invention has a good adsorption effect on various heavy metal ions, phosphates, nitrates and organic pollutants, and can remove various pollutants in water at one time, thereby simplifying the purification process.
[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly absorbent nonwoven fabric, characterized in that: The highly adsorbent non-woven fabric is obtained by immersing a non-woven fabric base fabric in a finishing liquid, and the non-woven fabric base fabric is made of the following raw materials: by weight, 70-80 parts of polypropylene, 15-55 parts of polyester particles, 5-10 parts of modified activated carbon, 3-5 parts of lubricant, 5-10 parts of antioxidant, 1-2 parts of heat stabilizer, and 5-8 parts of compatibilizer.
2. A highly absorbent nonwoven fabric as claimed in claim 1, characterized in that: The preparation method of the modified activated carbon comprises the following steps: (1) ball milling the biomass activated carbon; (2) The ball-milled biomass activated carbon and the activator are then mixed, placed in a tube furnace and heated to 600-800° C. under argon protection, and reacted at a constant temperature for 45-65 minutes to obtain modified activated carbon.
3. A highly absorbent nonwoven fabric as claimed in claim 2, characterized in that: The mass ratio of the biomass activated carbon to the activator is 1:1-3, and the activator includes potassium carbonate and potassium bicarbonate.
4. A highly absorbent nonwoven fabric as claimed in claim 1, characterized in that: The preparation method of the finishing liquid comprises the following steps: S1, adding chitosan to deionized water, reacting in a constant temperature oil bath at 75-85°C for 10-12h, then adding 2,3-epoxypropyltrimethylammonium chloride, continuing the reaction for 20-24h, cooling to room temperature after the reaction, filtering and drying to obtain quaternized chitosan; S2, adding quaternized chitosan and β-cyclodextrin to deionized water, stirring and mixing evenly, then dissolving S-acetylthiosuccinic anhydride and p-toluenesulfonic acid in DMF and adding them to the aqueous solution, heating to 120-160° C., reacting for 30-40 minutes, and after the reaction is completed, washing, filtering and drying to obtain a chitosan-β-cyclodextrin polymer; S3. First, mix the chitosan-β-cyclodextrin polymer and deionized water, then add sodium ethyl xanthate and sodium hydroxide, raise the temperature to 45-55° C., react for 1-3 hours, and after the reaction, precipitate with alcohol, wash, and dry to obtain a modified chitosan-β-cyclodextrin polymer; mix the modified chitosan-β-cyclodextrin polymer with deionized water to obtain a finishing solution.
5. A highly absorbent nonwoven fabric as claimed in claim 4, characterized in that: In step S1, the mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:2-3.
6. A highly absorbent nonwoven fabric as claimed in claim 4, characterized in that: In step S2, the mass ratio of the quaternized chitosan, β-cyclodextrin, S-acetylthiosuccinic anhydride and p-toluenesulfonic acid added is 2:4-6:2:0.2-0.
4.
7. A highly absorbent nonwoven fabric as claimed in claim 4, characterized in that: In step S3, the mass volume ratio of the chitosan-β-cyclodextrin polymer, sodium ethyl xanthate and sodium hydroxide is 1:0.3-0.4:0.02-0.
05.
8. A highly absorbent nonwoven fabric as claimed in claim 1, characterized in that: The lubricant is polyethylene wax and / or paraffin, the antioxidant is antioxidant 168 and / or antioxidant 3125, the heat stabilizer is one or more of calcium stearate, magnesium stearate and glyceride, and the compatibilizer is maleic anhydride grafted polypropylene.
9. A method for preparing a highly absorbent nonwoven fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) adding polypropylene, polyester particles, and modified activated carbon into a mixer and mixing them evenly, then adding a lubricant, an antioxidant, and a compatibilizer and mixing them evenly, granulating them through a twin-screw extruder, and vacuum drying to obtain a blend masterbatch; (2) Melting the blend masterbatch by screw extrusion to obtain a melt, pressing the melt into a spinning box at a pressure of 1-3 MPa, spinning, cooling, and pulling to obtain a fiber web, and hot-rolling the obtained fiber web on a hot rolling mill at 125-160° C. to obtain a non-woven fabric base fabric; (3) placing the finishing liquid in a slurry barrel, passing the nonwoven fabric base fabric through a pressing roller and a sizing roller, placing the sizing nonwoven fabric between two rubber pressing rollers of a pressing roller machine for extrusion, the pressing roller pressure is 4-8 kg, the rolling line speed is 160-180 m / min, and then drying in an oven at 100-120° C. to constant weight, thereby obtaining the highly absorbent nonwoven fabric.
10. The use of a highly absorbent nonwoven fabric according to any one of claims 1 to 8, characterized in that: The nonwoven fabric is used for aquaculture.
Citation Information
Patent Citations
Composite filtering media and filter method of superfine suspending matters in mariculture water
CN103109772B